2013
DOI: 10.1016/s0140-6736(13)60900-9
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and upper gastrointestinal effects of non-steroidal anti-inflammatory drugs: meta-analyses of individual participant data from randomised trials

Abstract: SummaryBackgroundThe vascular and gastrointestinal effects of non-steroidal anti-inflammatory drugs (NSAIDs), including selective COX-2 inhibitors (coxibs) and traditional non-steroidal anti-inflammatory drugs (tNSAIDs), are not well characterised, particularly in patients at increased risk of vascular disease. We aimed to provide such information through meta-analyses of randomised trials.MethodsWe undertook meta-analyses of 280 trials of NSAIDs versus placebo (124 513 participants, 68 342 person-years) and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
492
6
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,422 publications
(538 citation statements)
references
References 28 publications
12
492
6
8
Order By: Relevance
“…The discrepancy between our estimated 60% increased risk and the meta-analysis’ estimate for any stroke (1.18, 0.79 to 1.78) could be explained by our focus on ischaemic stroke 3. The incidence rate ratio for atrial fibrillation or flutter found in our study was lower than previously reported (1.73, 1.53-1.97),39 in part owing to our ability to control for healthcare seeking behaviour.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The discrepancy between our estimated 60% increased risk and the meta-analysis’ estimate for any stroke (1.18, 0.79 to 1.78) could be explained by our focus on ischaemic stroke 3. The incidence rate ratio for atrial fibrillation or flutter found in our study was lower than previously reported (1.73, 1.53-1.97),39 in part owing to our ability to control for healthcare seeking behaviour.…”
Section: Discussioncontrasting
confidence: 98%
“…Comparing diclofenac initiation with no NSAID initiation, the consistency between our results and those of previous meta-analyses of both trial and observational data provides strong evidence to guide clinical decision making. The Coxib and traditional NSAID Trialists’ Collaboration meta-analysis found a 40% increased risk of vascular events associated with diclofenac use versus placebo or no use (incidence rate ratio 1.41, 95% confidence interval 1.12 to 1.78), driven by an increased rate of myocardial infarction (1.70, 1.19 to 2.41) 3. Also in line with our results, the meta-analysis showed that diclofenac users had an increased risk of heart failure (1.85, 1.17 to 2.94) and vascular death (1.65, 0.95 to 2.85) 3…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we applied many of these comorbidities in our regression models, including continuous assessment of their presence. Use of NSAIDs has been associated with increased risk of HF and was therefore included in the model as well 23, 24. Although lower estimates were found (Model 2 compared with Model 1, Table 4), the IRRs were still significantly increased; thus, SA seems to be an independent risk factor for developing HF.…”
Section: Discussionmentioning
confidence: 99%
“…Because mortality due to cardiovascular disease is high in BE patients, "technical review on the management of Barrett's esophagus today" suggests screening for cardiovascular factors in BE patients and aspirin and statin use as warranted [45] . Because we have shown no benefit for non-aspirin NSAID use in BE patients with ischemic heart disease [53] and substantial cardiovascular side effects are expected [103,104] , use of non-aspirin NSAIDs should be withheld in patients with BE and cardiovascular co-morbidities, at least until more clinical data might justify their use.…”
Section: Future Directionsmentioning
confidence: 96%
“…Analyses showed that the excess risk was mainly attributable to an increase of about three quarters in the risk of major coronary events. Vascular death increased by about twothirds, heart failure risk roughly doubled, while risk for stroke was not affected [103,104] . Nitro-NSAIDs represent an NSAID subclass with lower risk for gastrointestinal bleeding [105] .…”
Section: Cost-effectiveness and Side Effects Of Nsaids Chemopreventionmentioning
confidence: 99%